2012
DOI: 10.1126/science.1228633
|View full text |Cite
|
Sign up to set email alerts
|

An Exon Splice Enhancer Primes IGF2:IGF2R Binding Site Structure and Function Evolution

Abstract: Placental development and imprinting co-evolved with parental conflict over resource distribution to mammalian offspring. The imprinted genes, IGF2 and IGF2R, code for the growth promoter insulin-like growth factor 2 and its binding inhibitor, mannose 6-phosphate/IGF2 receptor, respectively. M6P/IGF2R of birds and fish do not recognize IGF2. In monotremes that lack imprinting, IGF2 specifically bound M6P/IGF2R via a hydrophobic CD loop. We show that the DNA coding the CD loop in monotremes functions as an exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 66 publications
4
69
0
1
Order By: Relevance
“…The latter could be accomplished via regulating the bioavailability of the mitogenic insulin-like growth factor 2 that is both postnatally expressed in thymic epithelial cells (62) and upregulated in diseases (28), namely via internalization and subsequent degradation in lysosomes (12,63). 4) Furthermore, CD222's surface upregulation might play a role in T cell differentiation from the double negative to the double positive stage as CD222 Ab was reported to block T cell ontogeny (64).…”
Section: Discussionmentioning
confidence: 99%
“…The latter could be accomplished via regulating the bioavailability of the mitogenic insulin-like growth factor 2 that is both postnatally expressed in thymic epithelial cells (62) and upregulated in diseases (28), namely via internalization and subsequent degradation in lysosomes (12,63). 4) Furthermore, CD222's surface upregulation might play a role in T cell differentiation from the double negative to the double positive stage as CD222 Ab was reported to block T cell ontogeny (64).…”
Section: Discussionmentioning
confidence: 99%
“…We found that IGF2R has been shaped by putatively strong positive selection within reptiles and positively selected sites clustered on the IGF2R protein surface in domain 11, which is intimately involved in binding IGF1 and IGF2. Several of the positively selected sites on the protein surface of IGF2R in reptiles are essential for binding IGF2 based on mutagenesis studies and the crystal structure of the IGF2R-IGF2 complex (e.g., Y1542) (43)(44)(45) (Fig. 2C and Table S4).…”
Section: Positive Selection In the Iis/tor Hormones And Receptors Showmentioning
confidence: 99%
“…Labeled sites (IGF1 S37 and N251; human numbering) are known to affect IGF hormone and receptor binding (Table S4). (C) Domain 11 of reptile and mammal IGF2R with IGF2 oriented toward the binding pocket to demonstrate the clustering of positively selected sites on the reptile IGF2R binding surfaces (43,44). The magenta sites on reptile IGF2 and IGF2R were identified as coevolving amino acids using CAPS (46).…”
Section: Binding Proteins Exhibit Putative Truncations Of Important Fmentioning
confidence: 99%
“…One such evolutionary biochemical example is the initial acquisition and subsequent gain of affinity between the insulin-like growth factor 2 (IGF2) ligand and a single domain of a nonsignaling mannose 6-phosphate (M6P)/IGF2 receptor (IGF2R) (domain 11). The structural and functional basis of this evolutionary path, which has occurred over 150 million years of mammalian evolution, has been reported previously (2). The questions that we address in the present work are whether the IGF2:domain 11 interaction has reached an optimal state in the context of IGF2 activation of signaling receptors and in the ligand clearance function of M6P/IGF2R, and how far can we extend the binding interaction in terms of structural, biophysical, and functional properties.…”
mentioning
confidence: 88%
“…Domain 13 indirectly interacts with the AB loop of domain 11, breaking this interaction in the multiple-domain receptor, and contributes to the stability of the complex by decreasing the "off-rate" (k off ) of the IGF2 interaction (21). Mutations in the AB loop replace the effect of domain 13, increase the affinity for IGF2 (2,22), and facilitate subsequent determination of a solution structure of the 24.2-kDa complex of IGF2 with domain 11 AB3 that incorporated three mutations of the AB loop (also known as AB3 or E1544K, K1545S, and L1547V; K D = 15 nM) (2). The structural basis of the IGF2:domain 11 AB3 interaction occurs with a relatively fixed conformation of the CD loop on complex formation.…”
mentioning
confidence: 99%